Malnutrition of patients at hospital admission: prevalence and importance of early detection - Baraglia, Nancy (2020)
Background: The early identification of the nutritional status of patients admitted to a hospital has a beneficial impact on the control of medical care costs and therapeutic strategies aimed at those patients who require it. Nutritional screenings are used to detect nutritional risk, allow early intervention and influence the prognosis. Objective: To identify the prevalence of malnutrition in patients admitted to the Central Aeronautical Hospital of Argentina, evaluating what is the most efficient tool that would allow us to evaluate the patients’ nutritional status. Method: Cross sectional, observational, descriptive and unicentric study. Nutritional status was evaluated in 208 subjects at hospital admission, between August and November 2014, using the Malnutrition Screening Tool (MST), the Subjective Global Assessment (SGA) and measurement of anthropometric parameters. Results: MST and SGA scores indicated a higher proportion of patients with malnutrition in relation to the assessment of anthropometry parameters. Comparing the results obtained with MST and anthropometry methods, a statistically significant association was found between them, as well as the association between the results obtained by anthropometry and SGA. Most frequent pathologies associated with malnutrition status were those of infectious, metabolic and surgical origin. Conclusion: To restore the patient to health, it is important to identify the nutritional status on time when admitted to a hospital. SGA method is of choice in most health centers, however, due to the strong correlation with the MST, an easy method to apply, we consider that its use is an appropriate strategy for the systematic evaluation of patients at hospital admission.